Acneiform nevus. - Milano, A. (European Journal of Pediatric Dermatology, 2022)
By acneiform nevus or comedo nevus or inflamed follicular nevus is meant a skin mosaicism characterized by typical acne lesions that affect the pilo-sebaceous follicle and range from blackhead to nodule-cyst. Currently, it is preferred to speak of abnormal or pathological mosaicism in the presence of cells of at least two genotypes in an individual originating from a single zygote, which are responsible for a pathological phenotype; it is thus distinguished from the physiological mosaicism linked to those post-zygotic, fetal or post-birth mutations, which occur in all individuals and are not responsible for a pathological phenotype […].